Statistical polymer method: Modeling of macromolecules and aggregates with branching and crosslinking, formed in random processes - Freddy A. Romm; Oleg L. Figovsky (Discrete Dynamics in Nature and Society)
The statistical polymer method is based on the consideration of averaged structures of all possible macromolecules of the same weight. One has derived equations allowing evaluation of all additive parameters of macromolecules and their systems. The statistical polymer method allows modeling of branched crosslinked macromolecules and their systems in equilibrium or non-equilibrium. The fractal consideration of statistical polymer allows modeling of all kinds of random fractal and other objects studied by fractal theory. The statistical polymer method is applicable not only to polymers but also to composites, gels,associates in polar liquids and other aggregates.